2019
DOI: 10.24252/eternal.v51.2019.a15
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Talk and Instructional Language Choice: Two Problems Encountered in Efl Classroom

Abstract: When we agree with the internalization of a foreign language acquisition centered in the classroom, teacher talk plays the most important role to achieve the success of teaching and learning. However, a high intensity of teacher talk and the hesitation of instructional language choice become two common problems are usually faced. Therefore, it seems important to present a variety of literature reviews to be considered by teachers which may be used as the reference to solve the problem. This study presented the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…It was in line with the result of this study where English was the most frequent language used by the teacher. The result of this study was in contrast to the previous studies in which those studies showed that Bahasa was frequently used in classroom language by the students to elaborate and present their ideas, thoughts, and feeling meanwhile this study pointed out that the students were obligated to use English in discussion sessions and teacher used English dominantly (Julianti et al, 2016;Pratiwi, 2019). A more complex study is suggested to be conducted which focuses on investigating the language choice used in classroom language during online learning by using the result of this study as reference.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was in line with the result of this study where English was the most frequent language used by the teacher. The result of this study was in contrast to the previous studies in which those studies showed that Bahasa was frequently used in classroom language by the students to elaborate and present their ideas, thoughts, and feeling meanwhile this study pointed out that the students were obligated to use English in discussion sessions and teacher used English dominantly (Julianti et al, 2016;Pratiwi, 2019). A more complex study is suggested to be conducted which focuses on investigating the language choice used in classroom language during online learning by using the result of this study as reference.…”
Section: Discussioncontrasting
confidence: 99%
“…Bahasa is mostly used by students to give their ideas and information, bring a joke, and criticize other students' behavior. The language choice is used by English teachers in EFL classrooms in their talks and interactions with students (Pratiwi, 2019). It is also found that Bahasa is commonly used by teachers for translating difficult words found in English and explaining grammar.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher should be aware with his language choice in determining which language work best to deliver the knowledge in his teacher talk. Pratiwi (2019) believes that the choice of language in teacher talk influences the students' success and failure because the choice of language is the key to construct or obstruct the learner participation.…”
Section: Ribut Surjowati Heru Siswahjudiokomentioning
confidence: 99%
“…In countries where English is a foreign language, the acquisition of foreign language is closely determined by the influence of their mother tongue (Pratiwi: 2019) several theories supporting the use of L2 as the medium of interaction in the classroom discourse, there are several studies supporting vice versa. Mokhtar (2015) argues that code-switching is helping the students' understanding and it is efficient to avoid lengthy explanation.…”
Section: Ribut Surjowati Heru Siswahjudiokomentioning
confidence: 99%
“…In line with that, Cook (2000) in (Hermanto (2015) stated that teacher talk, which occupies a special place in the target language classroom, is closely related to the success of students' target language acquisition. It is a crucial factor because teachers construct or obstruct learner participation in classroom interaction through their choice of language (Pratiwi, 2018).…”
Section: Introductionmentioning
confidence: 99%